A novel pilot animal model for bone augmentation using osseous shell technique for preclinical in vivo studies. Issue 6 (7th August 2022) - Kamal, Mohammad; Al‐Obaidly, Sara; Lethaus, Bernd; Bartella, Alexander K.
Abstract: Objectives: Bone grafting is commonly used to reconstruct skeletal defects in the craniofacial region. Several bone augmentation models have been developed to evaluate bone formation using novel bone substitute materials. The aim of this study was to evaluate a surgical animal model for establishing a three‐dimensional (3D) grafting environment in the animal's mandibular ramus for bone augmentation using the osseous shell technique, as in humans. Materials and Methods: Osteological survey of New Zealand white (NZW) rabbit skull ( Oryctolagus cuniculus ): Initial osteological and imaging surveys were performed on a postmortem skull for a feasibility assessment of the surgical procedure. Postmortem pilot surgery and cone beam computed tomography imaging: a 3D osseous defect was created in the mandibular ramus through a submandibular incision. The osseous shell plates were stabilized with osteosynthesis fixation screws, and defects were filled with particular bone grafting material. In vivo surgical procedure: surgeries were conducted in four 8‐week‐old NZW rabbits utilizing two osseous shell materials: xenogeneic human cortical plates and autogenous rabbit cortical plates. The created 3D defects were filled using xenograft and allograft bone grafting materials. The healed defects were evaluated for bone formation after 12 weeks using histological and cone beam computed tomography imaging analysis. Results: Clinical analysis 12 weeks after surgery revealed the stability of the 3D grafted bone augmentation defects using the osseous shell technique. Imaging and histological analyses confirmed the effectiveness of this model in assessing bone formation. Conclusions: The proposed animal model is a promising model with the potential to study various bone grafting materials for augmentation in the mandibular ramus using the osseous shell technique without compromising the health of the animal. The filled defects could be analyzed for osteogenesis, quantification of bone formation, and healing potential using histomorphometric analysis, in addition to 3D morphologic evaluation using radiation imaging.